IRF2BPL gene variants with dystonia: one new Chinese case report - Fei Yang; Hui Li; Yi Dai; Ran Zhang; Jiang-tao Zhang (BMC Neurology, 2023)
Abstract Background The carriers of damaging heterozygous variants in interferon regulatory factor 2 binding protein-like (IRF2BPL), encoding a member of the IRF2BP family of transcriptional regulators, may be affected by a variety of neurological symptoms, such as neurodevelopmental regression, language and motor developmental delay, seizures, progressive ataxia and a lack of coordination, and even dystonia. Case presentation We report a Chinese boy who presented with dystonia, dysarthria, and normal development due to nonsense IRF2BPL mutation, with intact imaging and EEG findings but without developmental delays or seizures. Whole-exome sequencing revealed a novel nonsense variant IRF2BPL (NM_024496) Exon C.562C > T (p.Arg188*). Conclusion This case report presents a Chinese boy with a novel nonsense variant in IRF2BPL, displaying rapid progressive dystonia and dysarthria, without early developmental delay or epilepsy; expands the IRF2BPL phenotypes in the Chinese population; and raises awareness of patients with IRF2BPL.